PENINGKATAN HASIL BELAJAR MENULIS CERITA FANTASI DENGAN MENGGUNAKAN METODE PAKEM SISWA KELAS VIII-C SMP NEGERI 5 TENGGARONG TAHUN PELAJARAN 2018/2019 - NFN Jumairi (Kantor Bahasa Kalimantan Timur, 2019)
This study aims to improve learning outcomes of class VIII-C students of SMP Negeri 5 Tenggarong, academic year of 2018/2019, in writing fantasy stories using the Pakem method. It was conducted in 3 (three) cycles and each of them consisted of planning, action, observation, and reflection. Based on the results, it can be concluded that the use of Pakem method in the learning of writing fantasy stories can improve the learning outcomes of class VIII-C students of SMP Negeri 5 Tenggarong in the academic year of 2018/2019.